JISMONIY TARBIYA DARSLARIDA BASKETBOL ELEMENTLARINI O‘RGATIShNING METODIK YONDAShUVI - Arziev, Sh.; Kalmuratov, I. (SCIENCE and SOCIETY, 2025)
This article covers the methodological foundations for effectively teaching the elements of technique and tactics in basketball. During the research, we relied on the results of practical exercises conducted with students aged 10-16. The article also offers practical recommendations and advanced pedagogical methods for coaches.